2016
DOI: 10.5114/reum.2016.63661
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-modifying effects of oral avocado/soybean unsaponifiables in routine treatment of knee osteoarthritis in Poland. An open, prospective observational study of patients adherent to a 6-month treatment

Abstract: ObjectivesObservational studies provide insights into real-life situations. Therefore, we assessed the effects of oral avocado/soybean unsaponifiable (ASU) capsules on pain relief and functional ability in patients, while they were receiving a routine treatment for knee osteoarthritis (OA).Material and methodsAn open, prospective, observational 6-month study was conducted in 99 centers in Poland in a group of 4822 patients with symptomatic knee OA receiving one 300 mg ASU capsule/day as a routine medication. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
13
1
1
Order By: Relevance
“…Li et al reported significantly higher COMP levels associated with a higher Kellgren-Lawrence (K-L) grade. They suggested COMP as an appropriate diagnostic marker for subclinical knee OA but did not report the effect of celecoxib on COMP [21]; thus, their findings were not comparable to the current results.…”
Section: Rheumatologycontrasting
confidence: 98%
See 1 more Smart Citation
“…Li et al reported significantly higher COMP levels associated with a higher Kellgren-Lawrence (K-L) grade. They suggested COMP as an appropriate diagnostic marker for subclinical knee OA but did not report the effect of celecoxib on COMP [21]; thus, their findings were not comparable to the current results.…”
Section: Rheumatologycontrasting
confidence: 98%
“…However, ASU has been suggested as a useful treatment choice for symptomatic OA due to its anabolic, anticatabolic, chondroprotective, and anti-inflammatory effects [11]. At the clinical level, administration of ASU to OA patients significantly reduced patients' symptoms, improved their joint function, and resulted in reduced consumption of NSAIDs [11,21,22]. Although the usefulness of ASU for the treatment of OA has been reported by several studies, systematic reviews suggest better efficacy for knee OA compared with hip OA and conclude that its exact efficacy and safety, compared with routinely prescribed drugs, is still controversial [23].…”
Section: Rheumatologymentioning
confidence: 99%
“…13,15 Some observational and clinical studies have shown a significant improvement in functional ability and joint pain accompanied by a reduction in the proportion of patients using analgesics and NSAIDs from 58.8% to 24.9%. [16][17][18] Previous systematic reviews and metaanalysis have evaluated ASU in the treatment of OA. However, these studies were focused on several nutraceuticals and dietary supplements including ASU.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ASU on OA pain is somewhat unclear. In horses, ASU was found to have no effect on experimentally-induced lameness [ 8 ]; however, a mild improvement in symptoms has been observed in OA patients taking ASU for several months [ 9 , 10 ]. The aim of the current study was to evaluate the effect of a commonly used ASU, Arthrocen, on joint pain and inflammation using a rodent model of OA.…”
Section: Introductionmentioning
confidence: 99%